023 Development of a bedside motion capture system: a pilot study. (23rd August 2021) - Kopanidis, Paul; Lynch, Joe; Asikuzzaman, Md; Pickering, Mark; Perriman, Diana; Spratford, Wayne; Lueck, Christian
Abstract : Objectives: Pronator drift is one of many clinical signs that would benefit from detailed study, but this requires accurate measurement of movement in three dimensions. The Vicon system is currently considered to be the gold standard for measurement of limb kinetics in a movement analysis lab but it cannot be used at the bedside for many reasons. This study aimed to investigate a portable camera-based motion capture system (MCS) as a clinically-useful alternative. Methods: The MCS used two commercially-available cameras arranged so as to permit stereoscopic calculation of depth (i.e. distance from the cameras), and therefore a 3-D representation of movement at the shoulder, elbow and wrist. Data were obtained simultaneously from both movement capture and Vicon systems while three normal subjects simulated four scenarios of the pronator drift test in each limb. Outputs from Vicon and MCS were analysed using Matlab to determine root mean square error (RMSE) in XYZ coordinates. A priori, an acceptable difference was considered to be an average RMSE of < 10 mm. Results: Collectively, the studies generated 53, 424 sets of data. The average RMSE in the XYZ axis was 14.9 mm (range 5.0-20.3 mm). Inaccuracy was greatest at the wrist during trials involving larger degrees of pronation. Conclusion: The motion capture system was able to generate a 3-D trajectory of limb motion but further refinement is needed before it can be used for the purposes of clinical measurement.